2009
DOI: 10.1111/j.1467-8551.2008.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐organizational Cooperation and Environmental Change: Moderating Effects between Flexibility and Innovation Performance

Abstract: The paper investigates the moderator effect of inter-organizational cooperation in the relationship between workplace flexibility and innovation performance. This research question is important because innovation is dependent on the strategic integration of technological knowledge, requiring organizations to acquire new capabilities rapidly or to ensure the presence of knowledge that may be beyond existing internal capabilities. Inter-organizational cooperation constitutes a relevant mechanism for a firm to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 111 publications
(136 reference statements)
0
42
0
4
Order By: Relevance
“…Studies addressing resources in terms of time and money have repeatedly proven that resources available to projects are directly related to the projects' creativity levels (Cohen & Levinthal, 1990;Damanpour, 1991;Farr & Ford, 1990;Tushman & Nelson, 1990). It was found that organizations that provide training and employee involvement practices, use performance-based pay systems, enable flexible working hours, emphasize job variety and autonomy, and demonstrate more human resource flexibility enjoy higher levels of innovation (e.g., Martínez-Sánchez et al, 2009, 2011Shipton et al, 2006). Studies focusing on management attributes to innovation found that management support (Choi & Chang, 2009) and top managers' favorable attitude towards innovation (Damanpour & Schneider, 2006) are conducive to organizational innovation.…”
Section: Organizational Level Studiesmentioning
confidence: 99%
“…Studies addressing resources in terms of time and money have repeatedly proven that resources available to projects are directly related to the projects' creativity levels (Cohen & Levinthal, 1990;Damanpour, 1991;Farr & Ford, 1990;Tushman & Nelson, 1990). It was found that organizations that provide training and employee involvement practices, use performance-based pay systems, enable flexible working hours, emphasize job variety and autonomy, and demonstrate more human resource flexibility enjoy higher levels of innovation (e.g., Martínez-Sánchez et al, 2009, 2011Shipton et al, 2006). Studies focusing on management attributes to innovation found that management support (Choi & Chang, 2009) and top managers' favorable attitude towards innovation (Damanpour & Schneider, 2006) are conducive to organizational innovation.…”
Section: Organizational Level Studiesmentioning
confidence: 99%
“…In the process of interorganizational cooperation, fi rms combine resources to gain competitive advantage over competing fi rms. Interorganizational cooperation modifi es the internal fl exibility of fi rms and impacts their innovativeness (Martınez-Sanchez et al, 2009). In dynamic environments, an innovative inter-organizational cooperation off ers fi rms an ecosystem that increases their internal fl exibility, enhances their ability to combine resources in more novel ways, and thus respond innovatively to external environment (Martınez-Sanchez et al, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Inter-organizational cooperation provides design firms more opportunities to take advantage of flexibility for innovation performance by facilitating the access and dispersion of knowledge with the firms [20]. Inter-organizational cooperation is an increasingly important leadership focus because it influences the design organizational innovation in supply chain's effectiveness and knowledge management [3].…”
Section: Inter-organizational Cooperation Leadershipmentioning
confidence: 99%